2004
DOI: 10.1002/cphc.200400175
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Scattering Study of the Aggregation of Syndiotactic Poly(methyl methacrylate) in Solution

Abstract: Syndiotactic poly(methyl methacrylate (s-PMMA) may undergo aggregation in n-butyl chloride (n-BuCl) at temperatures below the theta temperature. The aggregation behavior of the s-PMMA with weight-average molecular weight M(w) =6.06 x 10(5) g mol(-1) was studied by a combination of static and dynamic laser-light-scattering experiments. A solution of concentration 1.12 x 10(-4) g mL(-1) was quenched from 50 degrees C (above the theta temperature in n-BuCl, 35 degrees C to 12 degrees C, and the aggregation proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…[28][29][30][31][32] Since the densities ͑2.4 g cm −3 ͒ of the silica prepared by same process without AKD particles were same to that of usual glass, the prepared samples correspond to SiO 2 glasses with pores. First, we would like to point out that our strategy was based on the template method and the sol-gel process of bulk SiO 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31][32] Since the densities ͑2.4 g cm −3 ͒ of the silica prepared by same process without AKD particles were same to that of usual glass, the prepared samples correspond to SiO 2 glasses with pores. First, we would like to point out that our strategy was based on the template method and the sol-gel process of bulk SiO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…22 The authors investigated the possibility of the localization in the cavities at different generations, and found that it was realized in the cavity at the third generation, where "the n -th generation" means the number of hierarchical structure developed or the pore size distribution in a Menger sponge. [28][29][30][31][32][33] In this article, we will present the first experimental report on the creation of Menger sponge-like fractal body and the design of its fractality with a novel template method. 27 The essence was that the fractal surface structures enhanced the dewetta-bility.…”
Section: Introductionmentioning
confidence: 99%
“…Static and dynamic laser light scattering used as the main techniques in this work proved to be exceptionally powerful in the studies of various kinds of aggregation and association phenomena, especially in macromolecular systems. The suitability of these techniques for the study of association phenomena comes from the fact that intensity of scattered light as well as its other static and dynamic characteristics change very strongly upon association.…”
Section: Introductionmentioning
confidence: 98%
“…This can explain values of R g / R h ratio above 1, which are characteristic for loose particles. [ 48 ] The composition dependence of the shape parameter is also clearly seen in Figure 9 for PVP-PAA50 system. In x AA range between 0.1 and 0.3, ρ -parameter decreases from 0.8 to 0.6.…”
Section: The Structure Of Pvp-paa Interpolymer Complexesmentioning
confidence: 58%